"This is the way I pray": precatory language in the writings of Niccolò Machiavelli. Issue 2 (3rd April 2023) - Nederman, Cary J.; Lahoud, Nelly
ABSTRACT: Machiavelli's antipathy toward institutionalized Christianity has been very well documented, but less attention has been afforded to whether there might be some version of Christianity of which he would have approved. In the present paper, we investigate Machiavelli's misgivings about Christianity by inquiring into the role that he assigned to prayer, through which Christian "ideology" was operationalized. To our knowledge, nowhere in the large body of Machiavelli literature has anyone investigated systematically one such device for transmitting doctrinal principles into everyday practices. We contend that Machiavelli's formulation of prayer is consistently transactional and in line with pagan worship, especially as it was practised by Roman religion. We conclude that Machiavelli was not un-Christian, but that his formulation of prayer reveals one element of his criticism of the earthly church that he believed was complicit in twisting Christianity's potential for promoting commitment to love of country and civic liberty.